Investigation and Implementation of IoT Based Oil & Gas Pipeline Monitoring System - Zurkanain, Muhammad Arif; Subramaniam, Siva Kumar (International Journal of Recent Technology and Applied Science (IJORTAS), 2023)
Wireless Sensor Networks (WSNs) involve top potential technologies that will dramatically change the way of human living and working. Many scientific, industrial and environmental applications require real time information related to physical events like pressure, temperature or humidity. In the past the only way to transfer the sensed data to control center was through cumbersome and costly wires. But recent advancement in wireless networking enables WSNs to communicate the sensed real time event data wirelessly. WSNs have capabilities of sensing, processing and communicating which make them most suitable for monitoring different on and gas industries upstream, midstream and downstream operations which help to increase production, decrease the accidents, maintenance cost and malfunctioning.